PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN REWARD PADA SISWA KELAS III SDN 015 SAMARINDA ULU TAHUN PEMBELAJARAN 2018/2019 - Siska Oktaviani; Hani Subakti; Fantianus Maming Aples (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This research aims to improve the learning outcomes of grade III students at SDN 015 Samarinda Ulu learning year 2018/2019. The problem formulation in this research is how to improve the results of the study of IPA by using the reward in grade III students at SDN 015 Samarinda Ulu learning year 2018/2019. This study uses the Peneltitan class action. The research subject is a grade III student at SDN 015 Samarinda Ulu totalling 30 students. This study carried out as many as two cycles. The implementation stage of each cycle consists of planning, implementation, observation, and reflection. Data collection techniques using observation, tests, interviews, and documentation.The results showed that there was an increase in learning outcomes. This is seen from the value of the pre-cycle with an average value of 65.5 with a 14.2% submission and an incomplete percentage of 85.8% later on the I cycle of student learning results with an average test value of 69.5 with a percentage of 60% and incomplete percentage is 40% while in the cycle II student learning results with an average test value of 81.3 increases with a percentage of the submission of 86.7% and the percentage is not complete by 13.3%. Based on the results of the study, it can be concluded that the reward strategy can increase the results of SCIENCE study in grade III students at SDN 015-Ulu learning 2018/2019.